Understanding commodity markets to effectively address price increases and volatility in a post-COVID-19 world - Susan Newman; Sophie Van Huellen (Austrian Foundation for Development Research (ÖFSE), 2022)
Dependence on agro-commodity exports amongst low-income economies mean that they are uniquely vulnerable to balance of payment shocks. They are often also dependent on the imports of food crops and energy, resulting in a double burden in the post-COVID-19 period. In this paper, we review new and old theories of price formation in order to problematise price behaviour from the perspective of commodity dependent economies in the global South. In particular, we highlight the challenges of and imperative for macro-economic management and recent changes in commodity markets (namely financialization and supply chain restructuring) that must inform ways of managing price dynamics and mitigating implications for commodity dependent economies in light of the COVID-19 crisis and the war in Ukraine.
Keywords: 330; Commodity Prices; Commodity Dependence; Price Behaviour; Financialisation; COVID-19; Macroeconomic Management